Ectopic expression of ecdysone oxidase impairs tissue degeneration in Bombyx mori - Li, Zhiqian (Proc Biol Sci, 2015)
Metamorphosis in insects includes a series of programmed tissue histolysis and remolding processes that are controlled by two major classes of hormones, juvenile hormones and ecdysteroids. Precise pulses of ecdysteroids (the most active ecdysteroid is 20-hydroxyecdysone, 20E), are regulated by both biosynthesis and metabolism. In this study, we show that ecdysone oxidase (EO), a 20E inactivation enzyme, expresses predominantly in the midgut during the early pupal stage in the lepidopteran model insect, Bombyx mori. Depletion of BmEO using the transgenic CRISPR/Cas9 (clustered regularly interspaced short palindromic repeats/RNA-guided Cas9 nucleases) system extended the duration of the final instar larval stage. Ubiquitous transgenic overexpression of BmEO using the Gal4/UAS system induced lethality during the larval–pupal transition. When BmEO was specifically overexpressed in the middle silk gland (MSG), degeneration of MSG at the onset of metamorphosis was blocked. Transmission electron microscope and LysoTracker analyses showed that the autophagy pathway in MSG is inhibited by BmEO ectopic expression. Furthermore, RNA-seq analysis revealed that the genes involved in autophagic cell death and the mTOR signal pathway are affected by overexpression of BmEO. Taken together, BmEO functional studies reported here provide insights into ecdysone regulation of tissue degeneration during metamorphosis.